Efficacy and safety of intensive downstaging polypectomy (IDP) for multiple duodenal adenomas in patients with familial adenomatous polyposis: a prospective cohort study - Takeuchi, Yoji; Hamada, Kenta; Nakahira, Hiroko; Shimamoto, Yusaku; Sakurai, Hirohisa; Tani, Yasuhiro; Shichijo, Satoki; Maekawa, Akira; Kanesaka, Takashi; Yamamoto, Sachiko; Higashino, Koji; Fujisawa, Fumie; Ezoe, Yasumasa; Ishikawa, Hideki; Mutoh, Michihiro; Uedo, Noriya; Nojima, Masanori; Ishihara, Ryu (Endoscopy, 2023)
Background Patients with familial adenomatous polyposis (FAP) risk developing multiple duodenal adenomas (MDAs), leading to duodenal cancer and death. We investigated the efficacy and safety of intensive downstaging polypectomy (IDP) for MDAs integrated with new-generation procedures.Methods This prospective phase II study, conducted at a tertiary cancer center, enrolled patients with FAP who had MDAs. We performed IDP including cold snare/forceps polypectomy (CSP/CFP) and underwater endoscopic mucosal resection (UEMR). The primary end point was the downstaging of Spigelman stage at 1-year follow-up.Results 2424 duodenal polyps in 58 patients with FAP underwent IDP, including 2413 CSPs in 57 patients, seven CFPs in one patient, and four UEMRs in four patients. Only one major adverse event was observed (grade 3 hyperamylasemia) without clinical manifestations. We performed additional UEMR, CSP, and CFP for one, 12, and 22 patients, respectively, during initial follow-up. Overall, 55 patients completed protocol examination; the Spigelman stage was significantly reduced at the 1-year follow-up endoscopy (P < 0.001), with downstaging observed in 39 patients (71 %). Among the 26 patients with Spigelman stage IV at initial examination and protocol completion, 23 (88 %) showed downstaging. There was no major change in Spigelman stages from 1-year follow-up esophagogastroduodenoscopy to a median of 37 months (range 3–56).Conclusions IDP, including new-generation procedures, showed significant downstaging with acceptable adverse events for MDA in patients with FAP, even those with advanced-stage disease. Lesion selection for different resection techniques may be important for suitable and sustainable management of MDA in patients with FAP.